Catalytic oxygen activation versus autoxidation for industrial applications: a physicochemical approach. Issue 2 (26th September 2014) - Liu, Xi; Ryabenkova, Yulia; Conte, Marco
Abstract : The activation of oxygen for the functionalization of organic substrates may occur by means of transition metals or via autoxidation pathways affecting product selectivity and catalyst design. Abstract : The activation and use of oxygen for the oxidation and functionalization of organic substrates are among the most important reactions in a chemist's toolbox. Nevertheless, despite the vast literature on catalytic oxidation, the phenomenon of autoxidation, an ever-present background reaction that occurs in virtually every oxidation process, is often neglected. In contrast, autoxidation can affect the selectivity to a desired product, to those dictated by pure free-radical chain pathways, thus affecting the activity of any catalyst used to carry out a reaction. This critical review compares catalytic oxidation routes by transition metals versus autoxidation, particularly focusing on the industrial context, where highly selective and "green" processes are needed. Furthermore, the application of useful tests to discriminate between different oxygen activation routes, especially in the area of hydrocarbon oxidation, with the aim of an enhanced catalyst design, is described and discussed. In fact, one of the major targets of selective oxidation is the use of molecular oxygen as the ultimate oxidant, combined with the development of catalysts capable of performing the catalytic cycle in a real energy and cost effective manner on a large scale. To achieve this goal, insights from metallo-proteins that could find application in some areas of industrial catalysis are presented, as well as considering the physicochemical principles that are fundamental to oxidation and autoxidation processes.